Pengembangan Modul Litosfer untuk Meningkatkan Hasil Belajar Mata Pelajaran Geografi pada Kelas X Sekolah Menengah Atas - Siti Wa’dah (Universitas Pendidikan Mandalika, 2021)
The purpose of this research is to develop a lithosphere module for grade X SMA / MA students using the Dicky & Carey development model and to find out the effectiveness of the developed module. This research method uses research and development. The instruments used in this study were questionnaires and tests for each learning activity. The data analysis technique of this research uses descriptive statistical analysis. In this research, five modules have been developed, namely Module I (Structure of the Lithosphere Layer), Module 2 (Endogenous Energy), Module 3 (Exogenous Energy), Module 4 (Pedosphere), and Module 5 (Soil Erosion). Based on the results of field trials, this learning module has succeeded in showing benefits.